EP370/#492 Racial disparities in diagnostic evaluation of uterine cancer among medicaid beneficiaries. (4th December 2022) - Xu, Xiao; Chen, Ling; Wright, Jason
Abstract : Objectives: Black patients with uterine cancer are less likely than White patients to be diagnosed with localized tumors. To inform reasons for such disparity, we compared the quality of diagnostic evaluation received by Black versus White patients with uterine cancer. Methods: Using 2008–2019 MarketScan Multi-State Medicaid Database, we identified 858 Black and 1, 749 White patients with uterine cancer presenting with abnormal uterine bleeding (AUB). Quality of diagnostic evaluation was measured by delayed diagnosis (time between AUB reporting and uterine cancer diagnosis >1 year), not receiving guideline-recommended diagnostic procedures, and delayed time to first diagnostic procedure (time between AUB reporting and first diagnostic procedure >2 months). The association between race and the quality indicators was examined by logistic regressions adjusting for patient age, concurrent gynecologic conditions, comorbidities, and other characteristics. Results: Black patients were more likely than White patients to experience delayed diagnosis (11.3% versus 8.3%, p=0.01; adjusted OR, 1.71, 95% CI, 1.27–2.29) or to not receive guideline-recommended diagnostic procedures (10.1% versus 5.0%, p<0.001; adjusted OR, 1.94, 95% CI, 1.40–2.68). Even when they did receive recommended diagnostic procedures, Black patients were more likely than White patients to experience delay in time to first diagnostic procedure (10.9% versus 9.1%, p=0.16; adjusted OR, 1.46, 95% CI, 1.09–1.97). A lower proportion of Black than White patients underwent hysteroscopy (32.4% versus 39.6%, p<0.001) and transvaginal/pelvic ultrasound (61.8% vs. 73.3%, p<0.001). Conclusions: Black and White patients with uterine cancer differed in the quality of diagnostic evaluation received, which may be one plausible reason for their disparity in stage at diagnosis.